The Role of Organizational Culture Against Employee Loyalty in The Manufacturing Industry of Musical Instrument Assembly - Kahpi, Heri Safari; Salam, Anis Fuad; Riyanto, Indar; Fathurrohman, Fathurrohman; Nuryanto, Uli Wildan (International Review of Management and Marketing, 2020)
Organizational culture, an important aspect in a company to achieve its goals, as well as employee satisfaction within the company. Both of these aspects are determinants of employee loyalty. Given the importance of employee loyalty in the progress of the company, the determining aspects must have a positive influence on employee loyalty. The purpose of this study was to measure the effect of organizational culture variables and satisfaction on employee loyalty at musical manufacturing sector, Banten Province. This research using a quantitative approach with associative design methods. The population are employee at musical instrument manufacturing assembly at Banten Province with totally sample are 75 respondentsby using purposive sampling. This research using data collection techniques through initial interviews and questionnaires distributed to respondents by using SEM PLS for the analysis technique. The results showed that organizational culture had a positive and significant effect on employee loyalty. Organizational culture had a positive and significant effect on job satisfaction, job satisfaction had a positive but not significant effect on employee loyalty. Job satisfaction has not significantly mediated between organizational culture on employee loyalty. From the field observations and interview to the employee, most of employee loyalty still low, due to many numbers of contract workers. Management companies must immediately increase the workforce into permanent workers so that they feel comfortable working in the company. Keywords: Organizational Culture, Job Satisfaction, Employee Loyalty, Manufacturer Sector JEL Classifications: L2, M14 DOI: https://doi.org/10.32479/irmm.10053